Destination Branding Kabupaten Majalengka Oleh Dinas Pariwisata Dan Kebudayaan Kabupaten Majalengka - Nanda Mutiara Ulfah; Susie Perbawasari; FX Ari Agung Prastowo (PRoMEDIA, 2019)
In dealing with tourism issues such as the development of destinations that are not yet optimal, management of the tourism industry that is not yet optimal, as well as tourism resources that have not been integrated, it is necessary to do destination branding in Majalengka Regency. In addition, Majalengka Regency still does not have strong branding that can attract many foreign tourists to visit Majalengka Regency. The purpose of this study was to determine the stages of destination branding carried out by the Department of Tourism and Culture of Majalengka Regency in the development of tourism in Majalengka Regency. The method used is a descriptive qualitative research method with a post-positivistic paradigm. Data collection techniques used were interviews, observation, literature study, and documentation study. The results of this study indicate that the Department of Tourism and Culture of Majalengka Regency carried out the stages of market investigation, analysis, and strategic recommendations by conducting research mapping market potential analysis through three sources, namely experts from academia as facilitators; potential attraction of natural tourist attractions that are already running and already have decent natural visitors, and scoring techniques. At the Brand identity development stage, Majalengka Regency does not yet have a tourism destination identity because it is still in the process. For the stage of brand launch and introduction using three ways, namely special events, media, and involving the community. At the stage of brand implementation by making programs and tourism activities that involve pentahelix. And for the stages of monitoring, evaluation, and review related to the development of tourism destinations and statistical data of tourists visiting Majalengka Regency. Keywords: Destination Branding; Development; Tourism; Traveler; Majalengka Regency  Abstrak Dalam menghadapi permasalahan kepariwisataan seperti pengembangan destinasi yang belum optimal, pengelolaan industri pariwisata yang belum optimal, serta SDM Pariwisata yang belum terintegrasi perlu dilakukan destination branding di Kabupaten Majalengka. Selain itu Kabupaten Majalengka pun masih belum memiliki branding kuat yang dapat menarik banyak minat wisatawan luar untuk berkunjung ke Kabupaten Majalengka. Tujuan penelitian ini adalah untuk mengetahui tahapan destination branding yang dilakukan oleh Dinas Pariwisata dan Kebudayaan Kabupaten Majalengka dalam pengembangan pariwisata di Kabupaten Majalengka. Metode yang digunakan adalah metode penelitian deskriptif kualitatif dengan paradigma post-positivistik. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, studi pustaka, dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa Dinas Pariwisata dan Kebudayaan Kabupaten Majalengka melakukan tahapan market investigation, analysis, and strategic recommendations dengan melakukan riset pemetaan analisis potensi pasar melalui tiga sumber yaitu tenaga ahli dari akademisi sebagai fasilitator; potensi daya tarik objek wisata yang secara alami sudah berjalan dan sudah memiliki pengunjung alami yang lumayan, dan teknik skoring. Pada tahap Brand identity development, Kabupaten Majalengka belum memiliki identitas destinasi pariwisata dikarenakan masih dalam proses. Untuk tahapan brand launch and introduction menggunakan tiga cara yaitu special event, media, dan melibatkan komunitas. Pada tahapan brand implementation dengan membuat program serta kegiatan pariwisata yang melibatkan pentahelix. Dan untuk tahapan monitoring, evaluation, and review terkait dengan perkembangan destinasi pariwisata dan data statistik wisatawan yang berkunjung ke Kabupaten Majalengka. Kata Kunci: Destination  Branding; Pengembangan; Pariwisata; Wisatawan; Kabupaten Majalengka